2014
DOI: 10.1038/nature13896
|View full text |Cite
|
Sign up to set email alerts
|

mTORC1-mediated translational elongation limits intestinal tumour initiation and growth

Abstract: Inactivation of APC is a strongly predisposing event in the development of colorectal cancer1,2, prompting us to search for vulnerabilities specific to cells that have lost APC function. Signalling through the mTOR pathway is known to be required for epithelial cell proliferation and tumour growth3-5 and the current paradigm suggests that a critical function of mTOR activity is to upregulate translational initiation through phosphorylation of 4EBP16,7. This model predicts that the mTOR inhibitor rapamycin, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
299
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 270 publications
(323 citation statements)
references
References 43 publications
21
299
2
1
Order By: Relevance
“…Similar results have been reported in intestinal ischemia/ reperfusion injury and LPS-induced lung injury, further supporting our speculation (38,39). Recently, Faller et al (40), using multiple genetically engineered mouse alleles, found that S6K1/2, but not 4EBP1/2, was involved in intestinal regeneration and demonstrated that rapamycin functioned mainly through the mTORC1-S6K pathway rather than through the 4EBP1-eIF4E branch. These reports, together with our current study, suggest that mTORC1 plays an essential role in epithelial cells during acute injury mainly through the effector S6K1.…”
Section: Discussionsupporting
confidence: 73%
“…Similar results have been reported in intestinal ischemia/ reperfusion injury and LPS-induced lung injury, further supporting our speculation (38,39). Recently, Faller et al (40), using multiple genetically engineered mouse alleles, found that S6K1/2, but not 4EBP1/2, was involved in intestinal regeneration and demonstrated that rapamycin functioned mainly through the mTORC1-S6K pathway rather than through the 4EBP1-eIF4E branch. These reports, together with our current study, suggest that mTORC1 plays an essential role in epithelial cells during acute injury mainly through the effector S6K1.…”
Section: Discussionsupporting
confidence: 73%
“…6 In contrast to its possible oncogenic role, increased activation of eEF2K by treatment with rapamycin (an inhibitor of mTORC1), has been shown to dampen tumor growth in a model of colorectal cancer. 7 In line with these findings we found that NFR and other HIV-PIs elicited a sustained eEF2K activation that decreased protein synthesis, impaired cell proliferation and promoted cell-death. Moreover, eEF2K deficiency within tumors impaired NFR-mediated anticancer activity in immunocompromised mice, indicating that pharmacological eEF2K activation drives a tumor intrinsic response that impairs tumor growth.…”
supporting
confidence: 76%
“…Indeed, the eEF2K activity inhibits the translation elongation factor eEF2, which mediates GTP-dependent translocation of the ribosome, thereby promoting peptide chain formation. In the tumoral context, increased activation of eEF2K downstream of mTORC1 inhibition by rapamycin has been linked to APC-deficient adenoma growth arrest, suggesting that enhancing eEF2K activity can be beneficial in patients with colorectal cancer [24].…”
Section: Introductionmentioning
confidence: 99%